TEKNOLOGI 4G PADA JARINGAN GSM UNTUK KEBUTUHAN MOBILE INTERNET DI KOTA YOGYAKARTA - Santoso, Bambang Wahyu; Iswahyudi, Catur; Triyono, Joko (Jurnal Jarkom, 2015)
AbstractThe rise of 4G LTE networks with all the benefits can promise super-fast mobile data communications. Currently Â in Yogyakarta has been present 4G LTE technology that can be enjoyed by a few people, it is certainly affected by 4G device such a sim card 4G different sim cards 3G, data packets are used, a mobile device that supports 4G technology, as well as the area of coverage signal 4G uneven, to the area of signal coverage 4G in Yogyakarta city can be seen on the website of the network operator Indosat, and XL with coverage in the form of network points, but what about the location of base stations 4G on each network operator gsm, as well as the results of field testing on 4G signal quality in Yogyakarta. Â Surely this is a question of its own for some parties, who want speed internet at a faster devices using 4G signal.To answer these questions do research on signal quality 4G in Yogyakarta. With this research is expected that people who want to enjoy the services of 4G technology can determine the location of the nearest 4G base stations, the maximum distance 4G signal, optimal distance to be able to enjoy 4G services. and people can also knew the distribution pattern 4G signal in Yogyakarta city. Keywords: 4G, GSM, 4G base stations, Mobile Internet, Yogyakarta.